Steady forced convection flow and heat transfer in a nanofluid with passive control model - Siti Norfatihah, Zulkifli (2023)
The study of convective heat transfer and fluid flow has important engineering and industrial applications, for instance in the cooling of engine vehicles. Fluid such as water is commonly used as a heat transfer fluid because of its high heat capacity. Nevertheless, the limitation of water and the low thermal conductivity of other conventional heat transfer fluids could affect the efficiency of heat exchange. Therefore, a type of fluid with suspension of solid particles into base fluid, namely nanofluid was considered due to the property of nanofluid that enhances heat transfer. Mathematical models of nanofluid normally include a boundary condition that assumed nanoparticle volume fraction at the surface is constant. This boundary condition however might not be able to describe adequately the condition of nanofluid volume fraction at the boundary. Hence, a different boundary condition that considers nanoparticle mass flux at the boundary to be zero and adjusted accordingly is applied in this thesis. Recently, the use of micropolar fluid as a base fluid to nanofluid was applied in many studies. The local influence of intrinsic motion and microstructure of the fluid elements that are essential to this model of fluid can be advantageous as it can appropriately describe the types of fluid such as polymeric suspension and animal blood. Motivated by these reasons, numerical analysis of nanofluid and micropolar nanofluid flow with zero nanoparticle mass flux along with three different effects and geometries for each problem were deliberated in this thesis. The effects are viscous dissipation, Soret and Dufour, and chemical reaction, and the geometry that was investigated are moving plate, stretching plate, and wedge. In order to reduce the governing equations, series of transformation variables are used to transform the dimensional governing equations into dimensionless differential equations. The non-dimensional equations in ordinary differential equations were then solved numerically using Runge-Kutta Fehlberg. The results obtained were then compared with the limiting cases from previous study. This is done to determine the accuracy of the results published. Several parameters were examined in this thesis, namely Eckert number, Soret number, Dufour number, magnetic field, Brownian motion, thermophoresis, Lewis number, and Prandtl number. The results of reduced Nusselt number, skin friction coefficient, velocity profile, angular velocity profile, temperature profile, and concentration profile for each parameter were presented in tables and graph. It was found that the temperature and concentration profile shown a consistent result when there is an effect of viscous dissipation and chemical reaction. Temperature profile increases when thermophoresis parameter increases. In thermophoresis, the particle from the heated region is transferred to the cold region. Thus, this causes the nanofluid temperature to be increasing due to huge number of nanoparticles shifted from the hot region, which enhance the fluid temperature. Concentration profile was found to increase then decrease for both of the problems when the thermophoresis parameter and Brownian motion parameter increase. However, in the presence of Soret and Dufour, the temperature profile was found to increase when Brownian motion parameter increases, and concentration decreases then increases when the thermophoresis parameter increases. In comparison to the previous study, the difference is the temperature profile increases following an increase of Brownian motion parameter and concentration profile increase when thermophoresis increases.